RESEARCH DEVELOPMENT FIRE BLANKET - Aventi, . (MATTER: International Journal of Science and Technology, 2019)
Research development fire blanket is a follow-up study from previous researchers.This research is intended to obtain fire blankets from best fabric, using best chemicals, which are widely available on market and very easy to get on market, so that general public can easily obtain fabric and chemicals used for development this fire blanket in community.This study uses ten types of fabric, three types of fire retardant chemicals, and three types of preservative chemicals, so that fire blanket fabric according to its function can inhibit spread of fire / extinguish fire in event of fire, and not quickly damaged / torn /decay eaten by insects.The fabric of fire blanket is included in class 2, which is somewhat resistant to fire /rather non-flammable, under class 1 which is completely non-flammable, namely fabric two sides blue with mixture 6 C and mixture 2 C. Fabricantifire from Korea with mixture 2 C. Fabric jeans, corduroy, two sides red, and body rock, all with mixture 6 C.Other fabrics include grade 3, which is resistant to fire under grade 2.